A wideband circularly polarized CPW-fed substrate integrated waveguide based antenna array for ISM band applications - Sarosh Ahmad; Nabil Cherif; Salman Naseer; Umer Ijaz; Yanal S. Faouri; Adnan Ghaffar; Mousa Hussein (Heliyon, 2022)
This article presents a compact size circularly polarized substrate integrated waveguide (SIW) based wideband antenna array that serves industrial, scientific, and medical (ISM) band applications. A coplanar waveguide (CPW) technique is used to ensure the antenna size compactness. The proposed antenna is fabricated on a low-profile Rogers RT6002 substrate with a dielectric constant of 2.94, tanδ of 0.0012 and an approximate height of 0.76mm. The proposed design covers the frequency range from 2.15 GHz to 3.63 GHz (60.4%) while the axial ratio has a 3 dB bandwidth covering from 2.19 GHz to 2.51 GHz (13%) at the operating band of 2.45 GHz. The antenna is miniaturized and has a size of about 46.50 × 29 × 0.76 mm3. The simulation and experimental results are taken into consideration and there is a good promise between them. Hence, the antenna is a suitable applicant to be utilized for the applications in the ISM band.